Robust relationship between air quality and infant mortality in Africa - Heft-Neal, Sam; Burney, Jennifer; Bendavid, Eran; Burke, Marshall (Nature (London), 2018)
Poor air quality is thought to be an important mortality risk factor globally 1 – 3 , but there is little direct evidence from the developing world on how mortality risk varies with changing exposure to ambient particulate matter. Current global estimates apply exposure–response relationships that have been derived mostly from wealthy, mid-latitude countries to spatial population data 4 , and these estimates remain unvalidated across large portions of the globe. Here we combine household survey-based information on the location and timing of nearly 1 million births across sub-Saharan Africa with satellite-based estimates 5 of exposure to ambient respirable particulate matter with an aerodynamic diameter less than 2.5 μm (PM 2.5 ) to estimate the impact of air quality on mortality rates among infants in Africa. We find that a 10 μg m −3 increase in PM 2.5 concentration is associated with a 9% (95% confidence interval, 4–14%) rise in infant mortality across the dataset. This effect has not declined over the last 15 years and does not diminish with higher levels of household wealth. Our estimates suggest that PM 2.5 concentrations above minimum exposure levels were responsible for 22% (95% confidence interval, 9–35%) of infant deaths in our 30 study countries and led to 449,000 (95% confidence interval, 194,000–709,000) additional deaths of infants in 2015, an estimate that is more than three times higher than existing estimates that attribute death of infants to poor air quality for these countries 2 , 6 . Upward revision of disease-burden estimates in the studied countries in Africa alone would result in a doubling of current estimates of global deaths of infants that are associated with air pollution, and modest reductions in African PM 2.5 exposures are predicted to have health benefits to infants that are larger than most known health interventions. A 10 μg m −3 increase in the concentration of ambient respirable particulate matter is associated with a 9% rise in infant mortality in Africa and this increase is not affected by household wealth.